Contextualization of the Concept of Amal Saleh in the Textbook of Al-Quran Hadith at Madrasah Ibtidaiyah - Sukino Sukino (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2022)
The quality of human life is measured by good deeds to fellow creatures created by God. Therefore, understanding the concept of good deeds is so crucial for humans from an early age. The concept of good deeds is included in learning at Madrasah Ibtidiyah and requires a more contextual material analysis so that it is meaningful to students. This article aims explicitly to develop the concept of pious deeds taught in sixth-grade Madrasah Ibtidiyah. This study uses a qualitative approach, with an analytical descriptive way of concepts relevant to the theme. Data sources are texts of verses and hadiths, books, and articles with the theme of good deeds. Data analysis was carried out by reviewing, verifying, and comparing the concept of good deeds so that a concept was found that was by the research objectives. This study resulted in essential points, namely; 1) the concept of good deeds is the foundation of the relationship between all living beings in the natural world, and welfare and peace are influenced by understanding and implementing the concept of pious deeds. 2) implementing pious deeds can be done through alms to parents and close relatives; alms are given sincerely and done correctly, not hurting the feelings of others, 3) sharing knowledge with peers in the learning community, including pious deeds with worship values. 4) The main pious deeds are filial piety to parents (birr al-validation) in the form of alms of wealth, prayers, and good words